Amorphous–amorphous transition in a porous coordination polymer. Issue 52 (16th June 2017) - Ohtsu, Hiroyoshi; Bennett, Thomas D.; Kojima, Tatsuhiro; Keen, David A.; Niwa, Yasuhiro; Kawano, Masaki
Abstract : The amorphous state plays a key role in porous coordination polymer and metal–organic framework phase transitions. Abstract : The amorphous state plays a key role in porous coordination polymer and metal–organic framework phase transitions. We investigate a crystalline-to-amorphous-to-amorphous-to-crystalline (CAAC) phase transition in a Zn based coordination polymer, by X-ray absorption fine structure (XAFS) and X-ray pair distribution function (PDF) analysis. We show that the system shows two distinct amorphous phases upon heating. The first involves a reversible transition to a desolvated form of the original network, followed by an irreversible transition to an intermediate phase which has elongated Zn–I bonds.